Pembuatan Sistem Informasi Administrasi Manajemen Produksi Berbasis Website Pada PT. Semen Indogreen Sentosa - Michelle Magdalena; Yulia Yulia; Kartika Gunadi (Jurnal Infra, 2017)
PT. Semen Indogreen Sentosa is a company that supply ready-mix concrete. They still record manually using Microsot Excel and physical documents for all business procedures. Sales Order is crucial because in the first step of ordering plant division need to know the time availability. This step is causing a problem when the client must wait for the confirmation that takes a long time. Furthermore, because of the unavailability of information system, data processing is ineffective. Thus that’s why establishing information system for production management is needed.This website is created using HTML, PHP, JavaScript programming, language, and MySQL database. Application interface is created using Gentellela with Bootstrap template. Google Map is used to help measuring delivery time. The final result of the development of this website is able to integrate company information such as sales order records, purchase orders, materials stock and reports. This website also can help the compay to calculate the cost of goods. Delivery time can be measured faster and more accurate. Scheduling for production is easier and users from batching plant can see everyday orders directly.